MODERN SYSTEM OF PEDAGOGICAL EDUCATION OF ROMANIA - К. Тулін (Київський національний університет імені Тараса Шевченка, 2020)
The article is a study of the main directions of the current system of pedagogical education in Romania. It is established that the current reform of Romania's education began in 2002 and aims at the gradual integration into the educational space of the European Union. The current structure of the Romanian education system is examined and each component is analyzed in detail. The system of preschool education organization and its division into age groups is defined. Highlighted on features of secondary education. It is established that secondary education starts from primary school and the defined of the assessment system at this level is determined. It is noted that starting from the fifth grade there is a transition to high school, where the system of assessment is changed to the ten-grade system. It is noted that high school has two components: compulsory education and senior-level grades. The training of specialists is carried out by public and private institutions that have autonomy in carrying out their training activities. It is determined that Romania's higher education system is divided into three stages. The first degree of higher education is considered, which envisages two study options and may last from four to six years depending on the chosen specialty. It is determined that the second higher education degree in Romania includes a master's program and a postgraduate program. It is established that the third level of higher education is a doctorate, which lasts from four to six years depending on the form of study and ends with the award of the doctor's degree after successfully defending the dissertation. The degree of education of pedagogical staff in the system of preschool and primary education, as well as the minimum requirements for their further professional training in higher education institutions, are determined.

Стаття є дослідженням основних напрямків сучасної системи педагогічної освіти Румунії. Встановлено, що сучасна реформа освіти Румунії розпочалася у 2002 році і має на меті поступову інтеграцію до освітнього простору Європейського Союзу. Розглянуто сучасну структуру системи освіти Румунії та детально проаналізовано кожну складову. Визначено систему організації дошкільної освіти та її розподіл на вікові групи. Наголошено на особливостях середньої освіти. Встановлено, що середня освіта починається з початкової школи та визначено особливість системи оцінювання на цьому рівні. Зазначено, що починаючи з п'ятого класу відбувається перехід у середню школу, де змінюється система оцінювання на десяткову систему. Зазначено, що середня школа має дві складові: обов'язкову освіту та класи старшого ступеня. Підготовку фахівців здійснюють заклади державної і приватної форм власності, які мають автономію у здійсненні своєї діяльності навчання. Визначено, що система вищої освіти Румунії поділяється на три ступені. Розглянуто перший ступінь вищої освіти, який передбачає два варіанти навчання і залежно від обраної спеціальності може тривати від чотирьох до шести років.Визначено, що другий ступінь вищої освіти Румунії включає магістерську програму та аспірантуру. Встановлено, що третім рівнем вищої освіти є докторантура, яка триває від чотирьох до шести років, залежно від форми навчання, і закінчується присвоєнням ступеню доктора після успішного захисту дисертаційної роботи. Визначено ступені навчання педагогічних працівників у системі дошкільної та початкової освіти, а також мінімальні вимоги до їхньої подальшої професійної підготовки у закладах вищої освіти.
СУЧАСНА СИСТЕМА ПЕДАГОГІЧНОЇ ОСВІТИ РУМУНІЇ
Keywords: педагогічна освіта; Румунія; початкова освіта; середня освіта; вища освіта.; pedagogical education; Romania; primary education; secondary education; higher education.